Influence of supervisors’ attributes on the supervision outcomes among counselling interns - Ghazali, Nor Mazlina; Wan Jaafar, Wan Marzuki; Ahmad Tarmizi, Rohani; Mohd Noah, Sidek; Amat, Salleh; Anuar, Azzahrah; Aden, Edris; Yahya, Fatahyah (Lembaga Kaunselor, 2017)
Attributes consist of three subscales which include attractiveness, expertness, and trustworthiness. The supervisors’ attributes are measured using the Counsellor Rating Form Short (CRF-S), developed by Corrigan and Schmidt (1983). The study involved 120 students of the Bachelor of Education (Guidance and Counselling) with Honour from a public university in Malaysia who undergo the internship program at various organizations. Validity of the instrument for this study is .97 whereas its reliability is α = .85. Based on the findings of the study, there was a moderately strong relationship between the supervisors’ attributes and it has uniquely influenced the supervision outcomes. Implications of the findings for counsellor, supervisor, counselling interns and areas for future research were discussed.